SIMPLIFYING ASSUMPTIONS OF CONDENSING UNIT FMITE-ELEMENT MODEL AND THEIR INFLUENCE ON NATURAL FREQUENCY SPECTRUM - V. V. Naprasnikov; S. V. Krasnovskaya (Системный анализ и прикладная информатика)
The article touches upon such issues as mathematical model validity and accuracy of the obtained results, considering features of the finite element approach to condensing unit parametric modeling. Acceptable simplifying assumptions of a finite-element model of a condensing unit to define natural frequency spectrum is investigated and modal analyses of several simplified models are conducted. Eigensolution is implemented on a specific example of a system.